2004
DOI: 10.1177/089686080402400102
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and Electrolyte Transport across the Peritoneal Membrane during CAPD According to the Three-pore Model

Abstract: In the present review, we summarize the principles governing the transport of fluid and electrolytes across the peritoneum during continuous ambulatory peritoneal dialysis (CAPD) in “average” patients and during ultrafiltration failure (UFF), according to the three-pore model of peritoneal transport. The UF volume curves as a function of dwell time [V( t)] are determined in their early phase by the glucose osmotic conductance [product of the UF coefficient (LpS) and the glucose reflection coefficient (σg)] of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
4
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(177 citation statements)
references
References 73 publications
(111 reference statements)
10
159
4
4
Order By: Relevance
“…The peritoneal transporter category (or D/P Cr 4 h) was not associated with serum FGF23 levels in the present study, and previous studies have shown conflicting results regarding the effect of peritoneal transporter category on Pi elimination (29,30). Several clinical studies showed that peritoneal transporter category was associated with Pi clearance; patients with a high D/P creatinine value had greater Pi elimination through the dialysate (31).…”
Section: Renal Function and Fgf23 In Peritoneal Dialysis 387supporting
confidence: 44%
“…The peritoneal transporter category (or D/P Cr 4 h) was not associated with serum FGF23 levels in the present study, and previous studies have shown conflicting results regarding the effect of peritoneal transporter category on Pi elimination (29,30). Several clinical studies showed that peritoneal transporter category was associated with Pi clearance; patients with a high D/P creatinine value had greater Pi elimination through the dialysate (31).…”
Section: Renal Function and Fgf23 In Peritoneal Dialysis 387supporting
confidence: 44%
“…28 The latter assumption reflects that the potassium ion will be hydrated with a shell of water and act like a solute slightly larger than urea; this assumption is consistent with the lower mass transfer-area coefficient for potassium than urea across the peritoneum. 29 The ultrafiltration rate during the treatment was assumed constant and calculated as the predialysis body weight minus the postdialysis body weight divided by the treatment time; it was assumed that all fluid removed during the treatment was from the central distribution volume of potassium.…”
Section: Methodsmentioning
confidence: 99%
“…After peritonitis , ultrafiltration failure is the next most common cause of patients transferring to HD. Water moves out of the peritoneal capillaries and through the peritoneal mesothelium via aquaporin channels . During a PET test, water initially moves faster into the peritoneal cavity due to the large osmotic gradient, created by the fresh hypertonic glucose dialysate, whereas convective sodium movement into the peritoneal cavity moves slower through so called “small pores” .…”
Section: Discussionmentioning
confidence: 99%
“…As such, sodium sieving is used as an assessment of peritoneal free water transport and is used to investigate patients with ultrafiltration loss. Loss of sodium sieving has been linked to loss of aquaporin channels . Sodium sieving is greatest during the first 90 min of the PET test .…”
Section: Discussionmentioning
confidence: 99%